The Meaning of Happiness among Urban Children and Adolescents in Indonesia: A Qualitative Study Through Drawings - Handayani, Eko; Maulina, Dewi; Dahlan, Winarini W (UI Scholars Hub, 2025)
Urban children and adolescents face various stressors, including academic pressure, digital media exposure, and limited green spaces, which influence their happiness perception. This study aims to explore the meaning of happiness in children and adolescents living in Indonesia’s urban areas through qualitative research using a drawing-based approach. A total of 243 participants, aged 9-15, from elementary and junior high schools in Jakarta, were asked to draw